The Place Of Traditional Medicine In The African Society: The Science, Acceptance And Support - Antwi-Baffour, S.S.; Bello, A.I.; Adjei, D.N.; Mahmood, S.A.; Ayeh-Kumi, P.F. (American Journal of Health Research, 2014)
Traditional medicine (TM) has been described by the World Health Organisation (WHO) as one of the surest alternative means to achieve total health care coverage of the world’s population. In most African societies, traditional medicine plays an important role in the lives of millions who cannot access western medicine. In some areas, TM is part of the first set of response mechanisms for medical emergencies whilst in others the whole health system of the community is hinged on medicines rooted in local practice and belief. Although the relevance and values of TM is begining to gain recognition, African traditional medicine (ATM) still faces some challenges which underscore its scrutiny. This paper thus analyses the issue of science, acceptance and support for successful implementation of ATM and present the contemporary measures that are being taken to raise its standard to the level of western medicine.
Research Article
Keywords: Traditional Medicine; Western Medicine; African; Health